A cutaneous manifestation of acute lymphoblastic leukaemia mimicking urticaria pigmentosa. Issue 703 (May 1984) - Foulds, I. S.; Woodcock, B. E.; Slater, D. N.
Abstract : A 37-year-old female developed what appeared to be the typical cutaneous manifestations of urticaria pigmentosa. These preceded the peripheral blood changes of acute null cell lymphoblastic leukaemia and skin biopsy revealed that the cutaneous changes were due to leukaemic infiltration. Chemotherapy resulted in clearance of the rash. The importance of skin biopsy in patients presenting with suspected urticaria pigmentosa is emphasized.